Archean and paleoproterozoic crust generation events, Amparo complex and Serra Negra orthogneiss in southern Brasília Orogen, SE Brazil - De Oliveira, Marcos Aurelio Farias [UNESP]; De Assis Negri, Francisco; Zanardo, Antenor [UNESP]; Morales, Norberto [UNESP] (Elsevier, 2019)
The Amparo Complex and Serra Negra orthogneisses consists largely of Archean and Paleoproterozoic domains, which represent the older tectonizied basement of Ribeira Belt, southeastern portion of the Brasília Neoproterozoic Orogenesis. This is the subject of U–Pb SHRIMP and Nd and Sr isotopic and geochemical investigations aiming to increase the knowledge of these juvenile crustal domains. In this region, older Meso and Neoarchean rocks occur in physical proximity to younger Paleoproterozoic rocks of Serra Negra Orthogneiss. Mesoarchean gneisses with U–Pb zircon ages of 2956 Ma have a composition of TTG suites with TDM of 3176 Ma and a ƐNd(t) of −0.14, suggesting derivation from the partial fusion of older mafic rocks. Mafic (amphibolite) and ultramafic rocks are associated with these domains. Neoarchean porphyritic granites are associated with the former rocks, occurring as intrusive high-K granites. They have a TDM value of 3404 Ma and a ƐNd (2.7Ga) of −4.29, which demonstrates their derivation from older Archean crust. Paleoproterozoic units occur throughout the belt represented by granodioritic or tonalitic orthogneiss with intercalations of amphibolites and ultramafic rocks. In the extension to the west the units crop out in the Campinas region, and to the east are denominated Pouso Alegre Complex. They constitute a TTG-type granite-tonalite suite, as verified by their geochemical signatures, REE and incompatible elements, high Na/Ca ratios, and negative anomalies of Ta, Nb, and Ti. SHRIMP U–Pb zircon ages are between 2.09 and 2.16 Ga (Rhyacian) with TDM between 2.11 and 2.36 Ga and ƐNd(2.1 Ga) between +0.88 and + 3.18, indicating juvenile nature. Low 87Sr/86Sri ratios disclose a possible contribution of mafic precursors in their origin. Neoproterozoic Ediacaran ages of Ribeira Belt event are seen in zircon crystals of all samples analyzed for this study. The effects of this Neoproterozoic orogenic event on basement rocks resulted in anatexis, banding and folding of the older rocks. As suggested for the Paleoproterozoic Pouso Alegre Complex, it is possibly an important period of juvenile continental growth that, in association with the Archean gneisses, may be related to the southern end of the São Francisco Craton.
Keywords: Brasília Orogenesis; Juvenile crust; Meso to Neoarchean; Paleoproterozoic crustal evolution; Ribeira Belt; Zircon U–Pb geochronology